Radical Cyclization of Alkene‐Tethered Ketones Initiated by Hydrogen‐Atom Transfer. Issue 1 (4th December 2017) - Saladrigas, Mar; Bosch, Caroline; Saborit, Gisela V.; Bonjoch, Josep; Bradshaw, Ben
Abstract: An unprecedented C−C coupling reaction between alkenes and ketones by hydrogen‐atom transfer, using Fe(acac)3 and PhSiH3 in EtOH, is described. This mild protocol features high site selectivity and allows the construction of sterically congested structures containing tertiary alcohols and quaternary centers. The overall process introduces a novel strategic bond disconnection for ring‐closing reactions. Abstract : HAT trick : A C−C coupling reaction between unactivated alkenes and ketones by hydrogen‐atom transfer (HAT), using Fe(acac)3 and PhSiH3 in EtOH, is reported. As well as introducing a new strategic bond disconnection for the construction of sterically congested cyclic structures, it allows differentially substituted olefin types to be reacted in a site‐selective manner.